Predictors of e-cigarette initiation and use among middle school youth in a low-income predominantly Hispanic community - Gaddy, M. Yvonne; Vasquez, Denise; Brown, Louis D. (Frontiers in Public Health, 2022)
Introduction: E-cigarette use among middle and high school youth increased from 2.5 million in 2014 to 9.2 million in 2019, becoming the most common tobacco product used among youth. Hispanic youth, the largest ethnic minority in the United States, have higher rates of tobacco use, including e-cigarettes, than non-Hispanics. Identifying factors that put youth at risk for future e-cigarette use is vital to focusing prevention efforts. Informed by social cognitive theory, this study identifies predictors of e-cigarette uptake among e-cigarette naïve youth in a predominantly low-income Hispanic community. Methods: 1,249 students (6-8th grades) from two middle schools in El Paso, Texas consented to participate in this longitudinal survey during the 2016-2017 school year. The study sample for analysis was restricted to e-cigarette naïve students (n=862). Outcome measures were e-cigarette initiation and current use at follow-up. Logistic regression models tested six hypotheses about predictors of e-cigarette initiation and current use: 1) intention, 2) outcome expectations, 3) knowledge, 4) friendship network exposure, 5) normative beliefs, and 6) social acceptability. Results: Among e-cigarette naïve students at baseline, 8% (n=71) reported initiation at follow-up; of these, 3% (n=23) reported current use. Significant predictors of initiation were intention (AOR=2.46, 95% CI 1.69-3.59, p<.001), outcome expectations (AOR=1.73, 95% CI 1.14-2.61, p=.009), friendship network exposure (AOR=1.53, 95% CI 1.11-2.11, p=.01), normative beliefs (AOR=2.12, 95% CI 1.47-3.08, p<.001), and social acceptability (AOR=1.91; 95% CI 1.28-2.85; p=.002). Significant predictors of current use were intention (AOR=1.98, CI 1.07-3.69, p=.03) and friendship network exposure (AOR=1.69, 95% CI 1.06-2.70, p=.03). Conclusions: With the increasing popularity of e-cigarettes, age appropriate and culturally sensitive prevention strategies tailored at altering these predictive factors are essential in preventing future e-cigarette use.